Et ord af Guds Søn. Salmen »Sov sødt, barnlille« og dens tilblivelse - Ertner, Jørgen (Grundtvig-Studier, 1997)
A Word by the Son of God By Jørgen Ertner In the Jubilee Year 1983, a hitherto unknown Grundtvig letter emerged. The letter, dated May 28., 1844, was written to the vicar Ferdinand Fenger in Lynge near Soro, who was one of the clergyman friends that Grundtvig visited on his recuperational journey in May 1844 during the crisis that had hit him earlier that year. This letter throws new light on the hymn »Sleep sound, little child« (Sov sodt, barnlille) as regards its genesis as well as its content. Thus, on the basis of this letter, it is now possible to determine the chronological order of the composition of the stanzas, and to prove that the stanzas written first, presumably during the visit to Peter Rordam in Mem, are stanzas 1, 3 and 4 (following the counting in Den Danske Salmebog, DDS no. 488), while stanzas 2, 5 and 7 were composed later, presumably during Grundtvig’s stay at Gunni Busck’s in Stigs Bjergby, all stanzas with variants compared with the later known form. In particular, the letter, so far not used in Grundtvig research, sheds new light on the understanding of the significant variant in stanza 4 (DDS), the original expression ≫Maggot-Tongue≪, which can be traced back to Job 25,6. In the letter Grundtvig writes that the expression ≫Maggot-Tongue≪ is most fitting in an angel’s mouth for ≫us poor imitators of Him who said: ‘I am a worm, not a man’≪ (Psalm 22.7 in the Old Testament). It is ≫moreover an old medicine for my old Adam≪, Grundtvig adds, that is a medicine for his haughtiness, perhaps referring to the crisis of 1810. In very much his own manner Grundtvig combines Job 25,6 and Psalm 22,7 as an expression of the community with Christ in the hour of doubt and feeling forsaken by God. We are poor imitators of Christ, who in the midst of doubt and feeling forsaken by God maintained the community with God in prayer (cf. Psalm 22,2). Psalm 22.7 and 22,2 merge and become the Lord’s Prayer which, through Christ’s presence in the hour of doubt and feeling forsaken by God, becomes our prayer, which reaches God, who says ≫yes≪ to that prayer, because it is ≫a word by the Son of God≪. Thus it is the Lord’s Prayer, given to man in baptism that becomes Grundtvig’s help in the crisis. The thesis also points out how this understanding corresponds to the ≫discovery≪ of the Lord’s Prayer at which Grundtvig had arrived, at least from the late 1830s, a ≫discovery≪ on a par with ≫the matchless discovery of the Apostles’ Creed≪ as it has been shown by Christian Thodberg, an understanding of the Lord’s Prayer which is a precondition for the Lord’s Prayer being so helpful in the crisis as it turned out to be. In August 1884, in a letter to Peter Rordam, Grundtvig could write that through the crisis he had gained a new, clearer insight into life and the relation between Our Lord and man. At the end of the thesis it is shown how this ≫new≪ awareness finds its expression in a sermon on the 11th Sunday after Trinity where the Lord’s Prayer occupies a prominent position, a sermon that is echoed in a couple of contemporary hymns, where, for one thing, the word ≫maggot≪ about man occurs, and where, for another, it is said about Christ that He writhes like a worm in the earth. These are wordings that point back to the crisis in 1844 and to the hymn ≫Sleep sound, little child≪.